The Impact of Dynamic Capabilities on Achieving Sustainable Organizational Performance.: An Analytical Study of the Opinions of University of Kufa Professors - Durgham Hasan Abed; Abbas Mezeal (Iraqi Journal for Administrative Sciences, 2024)
Purpose: This study aims to study and determine the nature of the relationship between dynamic capabilities as an explanatory variable And sustainable organizational performance as a responsive variable. Methodology / Design: 135 questionnaires were distributed to professors at the University of Kufa who hold the title of Professor in all faculties of the university (21), and the retrieved questionnaires (129) were (127) valid for statistical analysis, (SPSS) as well as AMOS. Theoretical results: A knowledge gap on the interpretation of the relationship between the variables of research in addition to the researchers' quest to demonstrate the importance of sustainable organizational performance as an important means to achieve the high competitiveness of the organizations currently. Results: The research results in a set of results, including a direct significant effect between dynamic capabilities and sustainable organizational performance. Scientific results: The results of the research can be used as the organizations' interest and developing dynamic capabilities will lead to achieving sustainable performance and achieving its future goals. Originality / Value: The research came to fill a knowledge gap, which was the result of an earlier research that discusses the two research variables in one research model and the impact of this relationship on enhancing the social and competitive position of the organization.